Pemanfaatan Teknologi Musik Menengah dalam Meningkatkan Kompetensi Pembelajaran Seni Musik Berbasis Digital - Rozalvino Rozalvino (Pascasarjana Institut Seni Indonesia Padang Panjang, 2025)
The development of digital music technology has changed the orientation of music learning from instruction centred on notation, performance, and acoustic practice toward learning that integrates sound production, audio editing, MIDI sequencing, virtual instruments, and digital portfolio assessment. This study examines the use of intermediate music technology to improve competencies in digital-based music learning. Intermediate music technology is understood as a pedagogical stage that bridges basic digital literacy and advanced music production through the use of Digital Audio Workstation (DAW), MIDI, audio recording, editing, basic mixing, and collaborative production projects. The study aims to formulate a competency-oriented model for digital music learning by analysing how technology can strengthen technical, musical, creative, collaborative, and reflective abilities. A qualitative-descriptive method was employed through a directed literature review and document analysis of recent studies on music technology education, digital competence frameworks, DAW-based pedagogy, and technology-supported learning. The data were analysed thematically by classifying the findings into domains of learning objectives, technological tools, pedagogical strategies, competency indicators, and assessment models. The findings show that intermediate music technology improves learners' competencies by enabling them to operate digital tools, understand sound structures, produce musical works, evaluate audio quality, collaborate in digital projects, and document learning outcomes through portfolios. Effective implementation requires modular learning design, adequate infrastructure, teacher readiness, contextual learning materials, ethical awareness, and assessment rubrics that balance technical accuracy with musical expressivity. The novelty of this study lies in the formulation of an intermediate music technology learning model that integrates DAW-based production, MIDI practice, audio editing, basic mixing, and portfolio-based assessment as a coherent framework for digital-based music education.